THE ROLE OF HUMAN CAPITAL AND SOCIAL CAPITAL IN AGRICULTURAL INSTITUTIONAL DEVELOPMENT IN RURAL AREAS - Selly Oktarina; Anna Gustina Zainal; Ana Kuswanti; Eko Purwanto (Socio-Economics/Agribusiness Department, 2022)
The role ofÂ human capital and social capital is very needed in the development of farmer institutions.Â It is intended that existing farmer institutions can function optimally. This paper isÂ aÂ literatureÂ studyÂ based onÂ data andÂ relatedÂ journals.Â InÂ carrying out farmer institutional management, human capital can act as planners, organizers, implementers of activities and supervisors.Â In addition to human capital, social capital is also very important and needed in the development of farmer institutions.Â The role of social capital is to maintain cohesiveness, cooperation and carry out the tradition of deliberation (the element of trust), exchange of information, the tradition of â€œgotong royongâ€ and the tradition of social gathering (the element of reciprocity), carry out common goals and have an element of volunteerism (participation in the network and do it according to the rules. norm).